Transition Metal Complexation Studies on Heterocyclic Ligands - Vashi, R.T.; Shelat, C.D. (Asian Journal of Chemistry, 2010)
Two new ligands, HL1 and HL2 were synthesized from anthranilic acid and 5-bromo anthranilic acid, respectively. For this, quinazoline-4-one 8-hydroxyquinoline (QHQ) merged molecules were used. The complexes of first transition metals like Cu(II), Ni(II), Co(II), Mn(II) and Zn(II) with HL1 and HL2 have been prepared and characterized by physico-chemical methods such as elemental analysis, conductometric studies, magnetic susceptibility, infrared, NMR and electronic spectral data. The stoichiometry of the complexes has been found to be 1:2 (metal:ligand). An octahedral geometry around Co(II), Ni(II) and Mn(II), distorted octahedral geometry around Cu(II) and tetrahedral geometry around Zn(II) have been proposed. These complexes also been tested for their antifungal activities.